Preventive and therapeutic efficacy of halofuginone-lactate against Cryptosporidium parvum in spontaneously infected calves: A centralised, randomised, double-blind, placebo-controlled study - Klein, Pavel (Vet J, 2008)
The preventive and therapeutic efficacy of halofuginone-lactate (HFL) against Cryptosporidium parvum was evaluated in a study conducted from November 2004 to March 2005 on a dairy farm in Central Bohemia, Czech Republic, using 260 spontaneously infected calves. HFL (0.1 mg/kg/day) was administered orally for 7 days to 1-day-old and 8-day-old calves, respectively. In both treated groups the drug significantly, and in almost the same manner, decreased the intensity of diarrhoea (P < 0.001) and faecal oocyst count (P < 0.001) when compared to corresponding placebo groups. The only difference between both treated groups was the time of onset of symptoms of the infection. Over time, the clinical pattern of cryptosporidiosis in the animals treated at 8–14 days of age was similar to that seen in the groups receiving the placebo. In contrast, infection in the preventively treated group peaked about 10 days later but with the same intensity. The results of this study confirm the anticryptosporidial activity of HFL in calves, but show that the outcome of infection following preventive treatment is comparable to that observed in calves treated after the onset of symptoms.